The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1620/tjem.236.233
|View full text |Cite
|
Sign up to set email alerts
|

Transverse Movement of the Median Nerve in the Carpal Tunnel during Wrist and Finger Motion in Patients with Carpal Tunnel Syndrome

Abstract: Carpal tunnel syndrome (CTS) is the most common peripheral compression neuropathy of the upper extremity. Repetitive wrist and finger motion has been suggested as a major factor of pathogenesis of CTS. However, little is known about the pathomechanics of CTS. We aimed to evaluate the movement of the median nerve in the carpal tunnel during wrist and finger motions using transverse ultrasound in 21 patients with CTS (5 men and 16 women with mean age 69.0 years). We examined quantitatively the median nerve locat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 18 publications
1
35
0
Order By: Relevance
“…Currently, ultrasonography is used for diagnosing CTS, with a focus on detecting focal swelling of the median nerve in the carpal tunnel 17 . However, previous studies have suggested that a decrease in the transverse plane movement of the median nerve in ultrasonography is a characteristic feature of patients with CTS 18,19 .…”
Section: Discussionmentioning
confidence: 87%
“…Currently, ultrasonography is used for diagnosing CTS, with a focus on detecting focal swelling of the median nerve in the carpal tunnel 17 . However, previous studies have suggested that a decrease in the transverse plane movement of the median nerve in ultrasonography is a characteristic feature of patients with CTS 18,19 .…”
Section: Discussionmentioning
confidence: 87%
“…Dynamic ultrasound has been used to measure displacement differences in CTS patients versus healthy volunteers. In a transverse plane, movement of both the tendon and nerve within the carpal tunnel in CTS patients is inhibited (Filius et al, 2015; Nanno et al, 2015; van Doesburg et al, 2012; Wang et al, 2014). Normally, the median nerve moves dorsally between the superficial flexor tendons during flexing motions but this restriction in movement in CTS patients limits the ability of the nerve to translate while the tendons are loaded (Fig.…”
Section: Ssct and Carpal Tunnel Syndromementioning
confidence: 99%
“…Furthermore, in a previous study, we developed a technique to describe the detailed location of the median nerve as a coordinate within the carpal tunnel in healthy subjects and patients with CTS. 2,3 It is important to examine the location of the median nerve and its displacement amount as a coordinate to further comprehend the precise nerve position within the carpal tunnel during wrist and finger motions.…”
Section: Introductionmentioning
confidence: 99%